(untitled) (Marketing Journal, 2025)
This article also presents concepts about the relevance and importance of e- commerce today. Econometric analyses were conducted to study the impact of various factors on the development of the e-commerce system in an innovative economy. The author systematized and defined the factors influencing e-commerce and its development. In particular, the impact of technical, digital infrastructure, economic, social, legal and political, and cultural factors was assessed as the main factors influencing the development of e-commerce.